Advancements in understanding the relationship between Akkermansia muciniphila and the development of ulcerative colitis - Xu, Nie; Xiao, Xiaoping; Ma, Ying; Jing, Jing; Jiang, ShiCheng; Luo, KeYong; Li, Ying; Duan, Miao (Frontiers in Pediatrics, 2025)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease characterized by severe intestinal barrier dysfunction and immune dysregulation in patients, with limited clinical treatment options. Recent research highlights the important role of the gut bacterium Akkermansia muciniphila (AKK) in both the development and management of UC. AKK supports the integrity of the intestinal barrier by metabolizing mucins, enhances the production of tight junction proteins (Occludin-1/ZO-1), and influences immune responses by shifting macrophage polarization from M1 to M2, suppressing pro-inflammatory cytokines (IL-1β、IL-6、MCP-1), and activating anti-inflammatory pathways (SCFAs-SLC52A2/FFAR2、AhR). Clinical data indicate that the abundance of AKK in the intestines of patients with UC is significantly reduced, and this decrease is positively correlated with disease activity and relapse rates. Animal studies have demonstrated that adding AKK can restore the thickness of the mucus layer, lower inflammation scores, and improve the composition of gut microbiota. Importantly, the probiotic effects of AKK vary by strain; for instance, strain FSDLZ36M5 notably reduces colitis symptoms, while FSDLZ20M4 may worsen inflammation. These findings suggest that AKK or its metabolites, such as short-chain fatty acid(SCFAs), hold promise as therapeutic targets for the microbiota in patients with UC.Nonetheless, additional research on strain selection and clinical application is essential to refine treatment strategies. This article will review the correlation between the pathogenesis of AKK and UC, and explore the potential application value of AKK as a probiotic in children with UC, providing new insights for the prevention and treatment in patients with UC.